ANALISIS UPAYA GURU DALAM MENGHADAPI ANAK BERKESULITAN BELAJAR DI TK NEGERI PEMBINA PONTIANAK BARAT - Sari, Wiwin Purnama; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The research aims to describe the analysis of teachers' efforts in dealing with children with learning difficulties at Pembina Pontianak Barat Kindergarten. Descriptive qualitative research methodology is used. The group B class teacher at Pembina Pontianak Barat Kindergarten is the focus of this study. Interviews, observations, and documentation were the methods used for this study's data gathering. Data analysis was done, including gathering data, reducing it, presenting it, and generating conclusions. Triangulation is a method for validating data. The findings of this study are: 1. Teacher's efforts to communicate in conveying things related write reading the beginning of using examples of sentences and vocabulary that is easy for children to imitate and understand. 2. Efforts in refraction are made by teacher"™s by repeating the learning material of writing and reading the beginning so that childrend recall the vocabulary that have been taught. 3. The teacher's efforts in telling stories to stimulate children active in speech to reveal words in order to use easyly understand by children. The conclusion from this research awe that was prepared by the teacher in the analysis of the teacher's efforts in dealing with children has difficulty learning. The suggestions: the teacher delivers learning materials using mild language and is easy to understand by children, providing examples of easy to be imitate and apply by the child, and when telling stories, are expected to use styles or gestures and variaty of face expressions.